ANALISIS PERBANDINGAN EKSPOR DAN IMPOR KOMODITI UNGGULAN INDONESIA-CHINA SEBELUM DAN SETELAH PENERAPAN ACFTA - Putu Ayu Pramitha Purwanti, Anggraita Maya Dewi, (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 1 (2020): Vol 9 NO 1,Januari 2020 pp [ 1 - 232 ], 2020)
This study aims to first, test whether there are differences in the value of export transactions of superior commodities between Indonesia and China before and after the formation of ACFTA. Second, is there a difference in the value of superior commodity import transactions between Indonesia and China before and after the formation of the ACFTA. The study period was 2002-2017, namely 7 years before and 7 years after the establishment of ACFTA. The study uses secondary data where the transaction value tested is the total transaction value and the transaction value of each commodity. Before using the Wilcoxon test the normality test was used to see whether the data were normally distributed or not used to answer the research question. The results of the study concluded that overall, both export commodities and imported commodities experienced significant differences before and after the implementation of ACFTA. However, when viewed from each commodity, it was found that the export of rubber commodities did not experience significant differences before and after the implementation of the ACFTA.